Tim3 and PD-1 as a therapeutic and prognostic targets in colorectal cancer: Relationship with sidedness, clinicopathological parameters, and survival - Mokhtari, Zahra; Rezaei, Marzieh; Sanei, Mohammad Hossein; Dehghanian, Amirreza; Faghih, Zahra; Heidari, Zahra; Tavana, Shirin (Frontiers in Oncology, 2023)
Background: Colorectal cancer (CRC) is a heterogeneous disease that complicates predicting patients’ prognosis and their response to treatment. CRC prognosis is influenced by the tumor microenvironment (TME). The immune system is a critical component of the TME. Programmed cell death receptor 1 (PD-1) and T-cell immunoglobulin and mucin-domain containing-3 (Tim3) are inhibitory immune checkpoints that regulate immune response and may provide prognostic power. However, the effect of their expressions and co-expressions on the CRC prognosis remains unclear. Accordingly, this study aimed to investigate the prognostic value of the CD8, CD3, PD-1, Tim3 expression, and PD-1/Tim3 co-expression in patients with CRC. Materials and Methods: One hundred and thirty six patients with CRC who underwent curative surgery were enrolled in the study. Immunohistochemical staining was performed for PD-1, Tim3, CD8, and CD3, and the expression of each marker was evaluated in the center of the tumor (CT), invasive margin (IM), and adjacent normal-like tissue. Result: Our results indicated that high expression of PD-1 in IM was significantly associated with lower TNM stage, T-stage, M-stage, lack of metastasis, the presence of tertiary lymphoid structure (TLS), lack of recurrence (in the left-sided tumors), and larger tumor size (in right-sided tumors) (P<0.05). High expression of PD-1 in IM was also associated with improved overall survival (OS) in a subgroup of patients with high CD8 expression. High Tim3 expression in CT was associated with higher M-stage (M1) (in left-sided CRCs) (P<0.05). It was also associated with decreased OS in total cohort and left-sided CRCs and represented an independent prognostic factor for CRC patients in multivariate analysis. PD-1 and Tim3 co-expression had no synergistic effects on predicting OS. Conclusion: Our findings suggest that the clinicopathological and prognostic significance of immune system-related markers such as CD8, PD-1, and Tim3 depends on the primary tumor sides. We also showed that Tim3 could act as a prognostic factor and therapeutic target in CRC. This marker is probably a more preferred target for immunotherapy than PD-1, especially in left-sided CRCs.